1999
DOI: 10.1159/000045406
|View full text |Cite
|
Sign up to set email alerts
|

IgM/IgA Nephropathy in Callitrichids: Antigen Studies

Abstract: Renal tissues of callitrichids with IgM nephropathy were immunohistochemically examined for the participation of IgA in pathogenesis. In 58 histopathologically nephropathy-positive kidneys, IgM predominated in 20 cases and IgA in 7 cases, and in 31 cases both immunoglobulins were rated to be approximately equally involved. The disease, therefore, might be described as IgM/IgA nephropathy. The renal tissues and sera were also tested for nutritional antigens or antinutritional antigen antibodies, using immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 64 publications
1
18
0
6
Order By: Relevance
“…A histopathological feature of human IgA nephropathy was the eosinophilic mesangial deposit showing red in the MT-stained sections (D'Amico 1989). In a previous study, IgA immuno complex and anti-gliadin IgA were found in the common marmoset nephropathy (Brack et al 1999). Moreover, a wasting syndrome often occurs in common marmosets.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A histopathological feature of human IgA nephropathy was the eosinophilic mesangial deposit showing red in the MT-stained sections (D'Amico 1989). In a previous study, IgA immuno complex and anti-gliadin IgA were found in the common marmoset nephropathy (Brack et al 1999). Moreover, a wasting syndrome often occurs in common marmosets.…”
Section: Discussionmentioning
confidence: 88%
“…Previously, these renal lesions were described as ''IgM nephropathy'' because the frequency of the IgM deposition to the mesangium was high (Brack 1988(Brack , 1995Brack and Weber 1995). Also, it was reported that IgA was involved in this nephropathy (Brack et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Specific diseases of New World monkeys that can and have confounded research studies include: spontaneous atherosclerosis; Vitamin E/ selenium deficiency hemolytic anemia in owl monkeys, Heinz body anemia in C. jacchus, wasting marmoset syndrome and chronic idiopathic colitis in callitrichids (44), hepatic hemosiderosis in callithricids, owl monkeys and some of the other cebids (71,80); scurvy manifest as cephalohematomas in squirrel monkeys (93); glomerulopathies and nephritidies in many species (13,17,107); and parasitism especially acanthocephalidiasis, lung worms, and filariasis in wild-caught animals. Other health problems of which to be aware include: susceptibility to tuberculosis and toxoplasmosis; hepatitis in callitrichids and owl monkeys due to lymphocytic choriomeningitis virus; and the pathogenicity of human Herpesvirus simplex and squirrel monkey herpesviruses (H. saimiri and H. tamarinus) for owl monkeys and callitrichids with H.saimiri causing T-cell lymphomas.…”
Section: Lowenstinementioning
confidence: 99%
“…Chronic nephritis, especially glomerulonephritis, is seen fairly frequently in all nonhuman primates, but the callitrichids are especially prone to develop IGM/IGA nephropathy (17). Immune complexes directed toward parasitic and dietary antigens are hypothesized to play a role in the development of this lesion.…”
Section: Urogenitalmentioning
confidence: 99%
“…Either misrouting of IgA-committed B cells and their plasma cell progeny from the site of physiological induction [78, reviewed in 92] or exposure of an immune host to antigen via a novel portal of entry [notably 31, 33, 35, 38] can contribute to defects in the usual barrier to antigen penetration of mucosal surfaces. Mucosal inflammation [52,58,75,78] and defects in mucosal barrier function [10,[53][54][55][56][57][58]61] also improve entry of antigen from mucosal lumens into the body proper. Each of these four mechanisms simultaneously drive production of structurally altered IgA by modulating and/or hyperstimulating the immune system while favoring formation of IgA complexes with antigen, which are more nephritogenic [96][97][98][99].…”
mentioning
confidence: 99%